2020
DOI: 10.1021/acs.chemrev.0c00793
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Medium-Sized Rings by Gold Catalysis

Abstract: Compounds having cyclic molecular frameworks are highly regarded for their abundance and diverse utilities. In particular, medium-sized carbocycles and heterocycles exist in a broad spectrum of natural products, bioactive therapeutics, and medicinally significant synthetic molecules. Metal-mediated methods have been developed for the preparation of compounds containing a medium-sized ring (MSR) through cyclization of different classes of substrates and acyclic precursors. This review focuses on the methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(74 citation statements)
references
References 186 publications
0
74
0
Order By: Relevance
“…On the other hand, the propensity of gold catalysts to activate π‐bonded systems has created opportunities to discover numerous hitherto unknown organic reactions [6–34] . Gold catalysis in organic reactions has been generally understood and simplified through the concepts of frontier orbitals, relativistic effects, and π‐Lewis acidity [35–37] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the propensity of gold catalysts to activate π‐bonded systems has created opportunities to discover numerous hitherto unknown organic reactions [6–34] . Gold catalysis in organic reactions has been generally understood and simplified through the concepts of frontier orbitals, relativistic effects, and π‐Lewis acidity [35–37] .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Theh igh p-Lewis acidity of cationic gold(I) complexes allow them to activate various unsaturations such as alkynes,a llenes and also alkenes towards intra-or intermolecular nucleophilic addition. [2] During the process,t he ligands carried by the gold(I) center play am ajor role in terms of stability,a llowing low catalyst loadings,m odulation of activity,a nd selectivity. [3] Furthermore,t he linear coordination of gold(I) complexes that positions the ancillary ligand opposite to the substrate and thus to the outer-sphere attack of the nucleophile renders asymmetric gold catalysis achallenging goal.…”
Section: Introductionmentioning
confidence: 99%
“…When p ‐Ns was used, no significant change in the reactivity compared with the model system was noticed ( 2 p , 66 %); thus, we concluded that spatial interaction of the nitro group is not significant to enhance the cyclization reaction. This reaction is also applicable to oxacycle formation ( 2 q , 39 %) by using an oxygen‐tethered substrate [7a] . Finally, a nucleophilic N ‐Boc protected indole was employed as a cyclization precursor.…”
Section: Resultsmentioning
confidence: 99%